The Austere academy - Snicket, Lemony; Helquist, Brett (London : Egmont Books, 2002)
As their outrageous misfortune continues, the Baudelaire orphans are shipped off to a miserable boarding school, where they befriend the two Quagmire triplets and find that they have been followed by the dreaded Count Olaf.
Includes audiobook.
Keywords: Humorous fiction; Orphans -- Fiction